The application of waste brass cartridges for gamma radiation shields and bullet proofing - W.B Qurix; L.C. Edomwonyi-Otu; J.K. Aremu; G.J. Ibeh; S.G. Bawa; D. Jise (Journal of Materials Research and Technology, 2020)
This report shows the results of the investigations into the possible use of waste brass cartridges for gamma-ray shields and bullet proofing. The increasing usage of bullets and the almost inert nature of the resulting waste cartridges is an environmental concern that is pushing a rethink. Waste brass cartridges were collected from different military institutions and washed. Some of the cartridges were cut to required sizes and prepared for elemental composition, surface morphology and crystallographic analyses. The results showed that the waste cartridges contained appreciable amount of brass and therefore adequate for intended use. The waste brass cartridges were then processed into different sizes and thickness (5 mm, 10 mm, 20 mm) for the gamma radiation tests using both Thermal Neutron Spectroscope and NaI(Tl) Gamma Spectroscope. Ballistic tests were also conducted for different material thickness and shooting range up to 100 m. The results showed that the 5−20 mm thick processed waste brass plates successfully shielded gamma-rays of up to 150 keV as applicable in general practice. At increased radiation energy, the transmitted intensity was found to decrease with increased material thickness for all energy levels. Models for relating the energy transmittance and material thickness were developed for different energy source and intensity up to 1500 keV. The mixture of lead and reprocessed brass had excellent shielding properties too, however holes resulting from improper mixing were observed. The optimal processing procedure and mixing ratio of the brass with lead to reduce the usage of lead in radiation shielding in currently being investigated. In addition, the projectile penetrated the sample materials at investigated thicknesses and shooting range. Effort is currently on to enhance the processing and make it suitable as a material for bullet proof purposes.